Management of Hydrocoelom in an Axolotl (Ambystoma mexicanum) - Şeyma Sueda Cirit; Şinasi Borgahan Deniz; Burhan Cirit; Abdulahad Bayraktar (Veterinary Medicine and Science)
ABSTRACT A 3‐year‐old axolotl (Ambystoma mexicanum) presented with anorexia, weakness and abdominal swelling due to hydrocoelom. According to the anamnesis, the symptoms had occurred 3 months prior. The radiographic and ultrasonographic examinations revealed that these symptoms resulted from the fluid accumulating in the coelomic cavity. Then, the habitat of the axolotl and the fluid in the coelomic cavity were inspected. Then, the patient's hydrocoelomic fluid was drained and medical treatment was performed. In addition, habitat arrangement and diet were changed. At the follow‐up visit 1 week later, the patient reported a significant decrease in hydrocoelom and a significant increase in appetite and mobility. Laboratory results showed no microbiologic growth in the sample taken from the coelomic cavity. The patient remained healthy during a 1‐year follow‐up. The last follow‐up examination revealed a significant decrease in all of the symptoms. In conclusion, non‐infective hydrocoelom was observed in an axolotl, and medical treatment was performed.